The image of masculinity in the novel the death of a former minister by Nawel El Saadawi - Chandraningtyas, Anggita Tri; Mukti, Salsa Faradila; Permata, Zezyana Ledys; Gregorius, William Chandra; Al Kindi, Musyarof 'Ibad; Citra, Calysta Utama Die; Hasna, Sulis Fatihatul; Pamungkas, Onok Yayang (Journal of Language, Literature, Social and Cultural Studies, 2026)
This study explores the construction of masculinity in Nawal El Saadawi’s The Death of a Former Minister, examining how male identities are shaped by and complicit in patriarchal power structures. Building on gender theory and previous work on gender inequality in the same text, the research focuses on how men are positioned as agents of marginalization, subordination, stereotyping, and violence within familial, political, and social spheres. Using a qualitative, descriptive textual method, the novel’s short stories are subjected to close reading, supported by Mansour Fakih’s framework of gender injustice and relevant feminist theories of masculinity. The analysis traces recurrent images of male authority—husbands, officials, religious and political figures—and interrogates how their bodies, language, and sexual power sustain a dominant masculine ideal that normalizes women’s inferiority, objectification, and abuse. The study concludes that El Saadawi represents masculinity not as a neutral or natural identity, but as a historically and culturally produced position of privilege that is deeply implicated in gendered oppression. At the same time, cracks within this model—moments of guilt, fear, or failure—suggest possibilities for critiquing and destabilizing hegemonic masculinity in Arab patriarchal contexts.